PENGARUH KEPUASAN KERJA DAN LOYALITAS KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA KINERJA KARYAWAN PT.HM.SAMPOERNA,TBK BATURAJA TIMUR SUMATERA SELATAN - Rani Anwar (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2018)
Purpose: The purpose of this study  was to determine the influence of job satisfaction and work loyalty to organizational citizenship behavior on employees’ performance at PT. HM Sampoerna TBK Baturaja Timur, South Sumatera.Metodh: This research used data from primary data collected directly from teh object under study using questionnaries. The analyses used are multiple linear analysis and coefficient of determination. The results of the research from the t-test analysis show that partially job satisfaction and work loyalty significantly influence Organizational Citizenship Behavior.Findings: The results of the F test show that job satisfaction and work loyalty simultaneously have a significant influence on Organizational Citizenship Behavior. The magnitude of the determination coefficient (R Square) is 94.6% while the remaining 5.4% is influenced by other variables. The result of this research are expected to be used as suggestion, either for PT. HM Sampoerna TBK Baturaja Timur, South Sumatera to managing the company or by researchers futher.Originality: -Keywords: job satisfaction and work loyalty.